PENGEMBANGAN STANDAR PROFESIONAL GURU DALAM RANGKA PENINGKATAN MUTU SUMBER DAYA MANUSIA - ASTUTI ASTUTI (Institut Agama Islam Negeri (IAIN) Bone, 2018)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, evaluating, and evaluating students in early childhood education through formal education, basic education, and secondary education. Teachers are positions or professions that require special skills as teachers . Furthermore, in exercising its professional authority, teachers are required to have a diverse set of abilities. Therefore, it is necessary to improve the professional standard of a teacher in carrying out his duties and responsibilities as a teacher, educator, and trainer so as to be able to realize the goals of national education, namely people who have faith and fear and have knowledge. Thus, the ideals of national development can be realized with the existence of quality human resources.